Tom's crossing : a western - Danielewski, Mark Z. (Pantheon Books, 2025)
"While folks still like to focus on the crimes that shocked the small city of Orvop, Utah, back in the fall of 1982, not to mention the trials that followed, far more remember the adventure that took place beyond municipal lines. For sure no one expected the dead to rise, but they did. No one expected the mountain to fall either, but it did. No one expected an act of courage so great, and likewise so appalling, that it still staggers the heart and mind of anyone who knows anything about the Katanogos massif, to say nothing of Pillars Meadow. As one Orvop high school teacher described that extraordinary feat just days before she died, Fer sure no one expected Kalin March to look Old Porch in the eye and tell him: You get what you deserve when you ride with cowards." -- Publisher annotation.